Comparative Study on the Effects of Urea and Organic Fertilizers on Growth and Yield of Mung Bean (Vigna radiata) - Nandita Yadav; Surbhi Chaturvedi; Akriti Maurya; Priyanka Pandey; Pritam Kaur; Akanksha Madan; Geeta Prakash (The Bioscan, 2026)
Organic fertilizers are recognized for their role in enhancing soil health and promoting sustainable crop production. This study investigated the impact of different fertilizers— compost, vermicompost, cow dung, liquid biofertilizer, and DAP granules—on soil pH, plant growth, and yield of Vigna radiata (mung bean) during the summer season in Delhi. Each treatment involved a 1:1 ratio of soil to fertilizer, and the mixtures were analyzed beforehand for inorganic nutrients such as chloride, sulphate, and nitrate, as well as pH levels. Plant growth was assessed through several parameters, including germination percentage, shoot and root length, fresh and dry biomass, chlorophyll concentration in leaves, and the pH of leaf extracts. Yield was evaluated based on the number of flowers and pods produced per plant. Among all treatments, vermicompost resulted in the highest germination rate, longest shoot and root lengths, greatest biomass accumulation (both fresh and dry), and the maximum number of pods. Conversely, liquid biofertilizer showed the lowest germination, control plants had the shortest shoots, and cow dung treatment resulted in the shortest roots. Compost and biofertilizer treatments produced the lowest fresh and dry weights, respectively. In conclusion, the results indicate that vermicompost is highly effective in improving soil conditions, supporting vigorous plant growth, and significantly boosting the yield of mung bean crops.